Time in the Upaniṣads - Cohen, Signe (2020)
The Upaniṣads (ca. 800 BCE) were composed during a transitional time period in Hinduism when Vedic ritual and cosmogonic ideas began to give way to new worldviews. The intriguing Upaniṣadic notions of time have received little attention in the scholarly literature compared to the elaborate models of cyclical time that develop in later texts. I propose, however, that the Upaniṣads represent a seminal reorientation in Hindu conceptions of time. We still find an older view of time in the Upaniṣads as something that marks the rhythms of the ritual year, but later Upaniṣadic texts begin to explore entirely new ways of thinking about time. I propose that the movement away from the more integrated view of the material and immaterial as one reality in the Vedas towards a radical dualism between the spiritual and the material in later Hindu thought informs many of the new ideas of time that emerge in the Upaniṣads, including that of time as an abstract construct. The authors of the Upaniṣads investigate—and ultimately reject—the notion of time itself as the cause of the visible world, ponder the idea that time is something that is created by a divine being in order to structure the world, speculate that time may be a mere intellectual construct, and postulate that the highest reality may be situated in a realm that is outside of time altogether.
Keywords: Hinduism; Upaniṣads; Time